Bile salt hydrolase and cholesterol assimilation potential of lactobacilli from Nigerian fermented foods and human sources - Duche, Rachael T; Nwagu, Tochukwu N; Singh, Anamika; Wandhare, Arundhati Ganesh; Sihag, Manvesh Kumar; Panwar, Harsh; Ezeogu, Lewis I (Indian Journal of Dairy Science, 2022)
Bile salt hydrolases (BSH) results in microbes releasing enzymes conferring physiological functions for both the producing organisms and the host and subsequently lower serum cholesterol. In recent years, these attributes have generated interest towards screening of lactic acid bacteria (LAB) for functional food production. In this present study, lactobacilli (n=34) (13 L. casei, 6 L. paracasei, 11 L. brevis, 3 L. pentosus and 1 L. plantarum) from varied sources viz. Nigerian fermented foods and human specimens were screened qualitatively and quantitatively for BSH activity using the direct plate assay and cell free extracts (CFE) of overnight cultures. To establish a correlation between BSH and cholesterol reduction, 12 isolates displaying high precipitation over bile salt agar plates, and high BSH enzyme activity in CFE were selected for in vitro cholesterol reduction assay. Results showed that 58% of the isolates from humans, and 36% from fermented food origin showed larger zones of precipitation. The highest BSH activity was exhibited by Lactobacillus casei GR4 (76mM) after 10 min of incubation, an isolate from fermented food. Isolates from human specimens expressed higher enzyme activity compared to those from fermented foods with significant increase (P<0.05) after 30 min incubation. Cholesterol level was variable as L. pentosus 8ST5 and 8ST7 had 2 and 4% cholesterol levels in the medium; while L. casei and paracasei group (Lactobacillus casei group, LCG) 3MB4, 8BM6, BK4 and L. brevis GR29 had 7%/ml each proving their application in food formulation, reduction of hypercholesterolemia, and as prophylaxis for controlling serum cholesterol levels.